2007
DOI: 10.1002/prot.21782
|View full text |Cite
|
Sign up to set email alerts
|

A general approach for developing system‐specific functions to score protein–ligand docked complexes using support vector inductive logic programming

Abstract: Despite the increased recent use of protein-ligand and protein-protein docking in the drug discovery process due to the increases in computational power, the difficulty of accurately ranking the binding affinities of a series of ligands or a series of proteins docked to a protein receptor remains largely unsolved. This problem is of major concern in lead optimization procedures and has lead to the development of scoring functions tailored to rank the binding affinities of a series of ligands to a specific syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 61 publications
0
27
0
Order By: Relevance
“…There are also significant differences in the experiments we conduct, e.g., in the various combinations of ML techniques and feature types we explore and the impact on BA prediction accuracy of various combinations of feature types and of limiting BLAST sequence similarity between binding sites of proteins in training and test complexes to assess the performance of ML SFs on novel targets. Prior to RF-Score, Deng et al applied kernel partial least squares modeling to geometrical features characterizing complexes [25] and Amini et al considered support vector regression [29] for protein-ligand BA prediction. Both of these studies showed promising results for ML methods, but considered small test sets.…”
Section: Introductionmentioning
confidence: 99%
“…There are also significant differences in the experiments we conduct, e.g., in the various combinations of ML techniques and feature types we explore and the impact on BA prediction accuracy of various combinations of feature types and of limiting BLAST sequence similarity between binding sites of proteins in training and test complexes to assess the performance of ML SFs on novel targets. Prior to RF-Score, Deng et al applied kernel partial least squares modeling to geometrical features characterizing complexes [25] and Amini et al considered support vector regression [29] for protein-ligand BA prediction. Both of these studies showed promising results for ML methods, but considered small test sets.…”
Section: Introductionmentioning
confidence: 99%
“…Despite advances in scoring algorithms, incorporation of protein and ligand flexibility and the treatment of solvent, all of which increase docking accuracy, 1,2 achieving proper ranking remains a significant and difficult problem that is largely unsolved. 3,4 A crucial component of a successful virtual screen with accurate ligand ranking is the experimental or modeling source of the receptor structure used for docking. High resolution crystal structures are typically chosen if available.…”
Section: Introductionmentioning
confidence: 99%
“…Mooij and Verdonk developed receptor-targeted scoring functions by modifying the atoms pair-wise interaction potential based on statistical analysis of complexes [29]. More recent studies used support vector machine and other approaches to develop target specific scoring functions [30,31]. However, none of the published methods has been applied on a large scale to achieve extensive protein-family coverage, or has been integrated into a standard docking tool.…”
Section: Introductionmentioning
confidence: 97%